Consumers’ Usage intention towards Mobile Healthcare Applications (MHA): A study of select cities in India - Ms. Heena Kashyap; Mr. Madan Lal; Mr. Sunny Makhija (Ramanujan International Journal of Business and Research, 2019)
This paper attempts to identify the factors influencing Consumers' usage intention towards mobile healthcare applications. There are many healthcare applications that are being launched in the market which would help consumers in preventing and curing the diseases. The promotional initiatives in healthcare market have made consumers conscious about their appearance and health such that demand for healthcare applications has increased considerably. Through thorough review of literature it was found that perception, trust and social factors influence usage intention of consumer patients towards mobile healthcare applications. The primary data has been collected from respondents belonging to region of Delhi- NCR, Chandigarh and Ludhiana. Smart PLS 2.0 software has been used for Confirmatory factor analysis of data where Correlation, t-statistics and composite reliability tests etc. have been applied. The results showed that perception, consumer trust and social factors influence the usage intention of consumers towards mobile healthcare applications. The mediation effect of consumer trust was also studied and it was found that there is partial mediation effect of consumer trust on both perception and social factors in relation to usage intention.